Optimization of conflicting properties via engineering compositional complexity in refractory high entropy alloys. (1st July 2021) - Kim, Il Hwan; Oh, Hyun Seok; Lee, Kwang Seok; Park, Eun Soo
Abstract: The strength-ductility (or thermal conductivity) trade-off is unavoidable in most conventional alloys due to the limited composition space. Herein, we propose a mechanism-based design strategy for concurrent optimization of high temperature (HT) strength, room temperature (RT) ductility, and HT thermal conductivity by considering atomic size misfit for solid-solution hardening and lattice distortion, and valence electron concentration for shear instability. As a test case, we extend the composition space of binary W-Ta alloys to W-Ta-V-Ti-Cr refractory high entropy alloys (RHEAs), and the present RHEAs (e.g. WTaVTiCr) exhibit superior HT strength (1210±43 MPa at 1073 K) and RT ductility (23.4±5.7%). Further, we show that the thermal conductivities of the present RHEAs increase with increasing temperature, and theoretically can reach to 40% of that of pure W at 2000 K. This work thus provides a general design rule of RHEAs that enables effective utilization of compositional complexity for potential applications. Graphical abstract: Image, graphical abstract